Methodological approach to assessment of organizational resources of the productive activity - Miller, Alexander (Serbian Journal of Management, 2017)
The purpose of this article is to solve the problem connected with development of theoretical and methodological provisions of formation of the assessment procedure of organizational resources of the productive activity. Theoretical results of our research are: improvement of the concept of development of organizational resources of the productive activity; identifying the impact of organizational resources on the productive activity; justification of the basic principles of formation of the assessment system of efficiency of the organizational resources’ use. We proposed a unified methodological approach allowing to combine the complexity of assessment of both quantity of core resources of the productive activity and organizational resources, which significantly develops traditional systems of the productive activity management based on identifying quantitative parameters of the subsystems, their assessment, comparison and analysis. We also substantiated our opinion on assessment of organizational resources’ values. It is focused on the development of the productive activity and allows to use the developed tools of the methodological approach for forecast assessment of the impact of the quantity of core resources, used in the productive activity, and organizational resources of the productive activity on the economic results of the enterprise.